2019
DOI: 10.3892/ijmm.2019.4339
|View full text |Cite
|
Sign up to set email alerts
|

Kappa opioid receptor agonists improve postoperative cognitive dysfunction in rats via the JAK2/STAT3 signaling pathway

Abstract: Postoperative cognitive dysfunction (POCD) is a common and well-known complication following surgery, particularly cardiopulmonary bypass (CPB) surgery. There are currently no suitable treatments for POCD, which is associated with increased illness and mortality rates. The present study aimed to identify a novel treatment for POCD. The protective effect of kappa opioid receptor (KOR) agonists on POCD in rats following CPB was determined and the regulatory mechanism of the Janus kinase 2/signal transducer and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…There is increasing evidence showing that the JAK2/STAT3 signaling pathway is activated in AD, and the inhibition of this (n = 6 in each group). **P < 0.01 vs. control group; # P < 0.05 and ## P < 0.01 vs. model group signaling pathway can alleviate neuroinflammation in AD [25,60]. In this study, we observed that in comparison with the control group, the expressions of hippocampal p-JAK2-Tyr1007 and p-Tyr705-STAT3 were augmented extensively in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…There is increasing evidence showing that the JAK2/STAT3 signaling pathway is activated in AD, and the inhibition of this (n = 6 in each group). **P < 0.01 vs. control group; # P < 0.05 and ## P < 0.01 vs. model group signaling pathway can alleviate neuroinflammation in AD [25,60]. In this study, we observed that in comparison with the control group, the expressions of hippocampal p-JAK2-Tyr1007 and p-Tyr705-STAT3 were augmented extensively in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 53%
“…Phosphorylated JAK2 promotes the activation of STAT3 at the Tyr705 site, which finally leads to neuroinflammation and apoptosis [ 57 59 ]. There is increasing evidence showing that the JAK2/STAT3 signaling pathway is activated in AD, and the inhibition of this signaling pathway can alleviate neuroinflammation in AD [ 25 , 60 ]. In this study, we observed that in comparison with the control group, the expressions of hippocampal p-JAK2-Tyr1007 and p-Tyr705-STAT3 were augmented extensively in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Following the activation of KOR receptors in stroke rats, injury inhibits glutamic acid release and NO production at the presynaptic membrane ( 43 ). Activation of KOR receptors also reduces neurotoxicity, improves the survival rate of damaged neurons, reduces neuronal apoptosis and the incidence of cerebral infarction and can reverse the memory impairment caused by CPB ( 44 ). Using the CPB rat model, the present study confirmed that oxidative stress served an important role in brain injury following CPB.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is a key player in regulating inflammatory gene expression and glial reactivity in CNS to various insults and stimulations ( 42 ). Specifically, JAK2/STAT3 signaling pathway was involved in POCD in rat model by increasing their phosphorylation, and inhibiting the levels of p-JAK2 and p-STAT3 could attenuate the symptoms of POCD in rats ( 43 ). A study has shown that VLX possesses anti-inflammation property ( 44 ).…”
Section: Discussionmentioning
confidence: 99%